المرائي الصوفية عند صوفية زواوة - ابو محمد الزواوي انموذجا - خلفات, مفتاح (جامعة الوادي - University of Eloued, 2016)
Boils down to the subject of this paper is to unveil the silent behavior of Sufis, which sparked heated debate among the pioneers of this trend and Nzeraihmmn jurists we mean by woolen Tartuffe, which classified the incident forensic science in the sect as across the spectrum of Ibn Khaldun For its part, the books of biography and character and has worked to promote the ideas of such a desire to prove the state of the guardian through the "divine dignity" which earned the status of religious and social which is what we are trying proven by hypocrite, Abu Mohammed Zawawi.
مقال
Keywords: المرائي الصوفية - صوفية زواوة - ابو محمد الزواوي